2018
DOI: 10.1525/mp.2018.35.5.561
|View full text |Cite
|
Sign up to set email alerts
|

Are Musical Autobiographical Memories Special? It Ain’t Necessarily So

Abstract: WE COMPARED YOUNG ADULTS' AUTOBIOGRAPHICAL (AB) memories involving Music to memories concerning other specific categories and to Everyday AB memories with no specific cue. In all cases, participants reported both their most vivid memory and another AB memory from approximately the same time. We analyzed responses via quantitative ratings scales on aspects such as vividness and importance, as well as via qualitative thematic coding. In the initial phase, comparison of Music-related to Everyday memories suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
1
2
1
Order By: Relevance
“…Almost all of the effects found here have parallels in autobiographical memory research using pictorial or word cues (Robin et al, 2019;Robin & Moscovitch, 2014;Simpson & Sheldon, 2020), suggesting that music affects autobiographical recall in a highly similar way to other common retrieval cues. This offers strong counterevidence to the common notion that music is "special" as a cue for autobiographical memories (see also Halpern et al, 2018). One notable exception is the divergence we found between negative valence/high-arousal and negative valence/low-arousal cues, in which the former evoked more positive memories than the latter; no such interaction between cue valence and cue arousal was found in a similar study using word cues (Simpson & Sheldon, 2020).…”
Section: Discussioncontrasting
confidence: 93%
“…Almost all of the effects found here have parallels in autobiographical memory research using pictorial or word cues (Robin et al, 2019;Robin & Moscovitch, 2014;Simpson & Sheldon, 2020), suggesting that music affects autobiographical recall in a highly similar way to other common retrieval cues. This offers strong counterevidence to the common notion that music is "special" as a cue for autobiographical memories (see also Halpern et al, 2018). One notable exception is the divergence we found between negative valence/high-arousal and negative valence/low-arousal cues, in which the former evoked more positive memories than the latter; no such interaction between cue valence and cue arousal was found in a similar study using word cues (Simpson & Sheldon, 2020).…”
Section: Discussioncontrasting
confidence: 93%
“…This suggests that, in general, music and food evoke phenomenologically similar autobiographical memories in everyday life and provides counterevidence to the idea that music is broadly ‘special’ as a retrieval cue. This bears similarity to the results of Halpern et al (2018), who found that autobiographical memories of music‐related and dining experiences did not significantly differ in terms of their degree of recollection, vividness, or emotionality. Instead, our results provide a more nuanced insight, indicating that, in comparison to food, music may be a more effective cue for involuntary autobiographical memories that are more directly related to one's personal life story and that these differences may be at least partially explained by differences between the cues themselves and the situations in which the memories occurred.…”
Section: Discussionsupporting
confidence: 89%
“…Second, we compared MEAMs and food-evoked autobiographical memories (FEAMs) between groups of young and older adults. Previous research has indicated that comparing music-related memories against any other autobiographical memory a participant experiences can produce results in which MEAMs are rated as more vivid and emotional than other memories simply because the search space for 'other' memories is considerably larger (Halpern et al, 2018). Hence, we chose to compare music against another specific cue that was similar on several key properties.…”
Section: The Present Studymentioning
confidence: 99%
“…Interestingly, both of these studies highlight populations for which music may not necessarily be the most useful memory cue: Baird et al (2020b) identified that for individuals with bvFTD, music may require multiple exposures in order to evoke memories, and Sakka and Saarikallio (2020) identified that music can evoke negative memories in persons with depression. These two studies highlight the importance of reminding researchers, as well as the general public, that music is not always a benign or allpowerful cue for memory retrieval (see also Halpern et al, 2018;Silverman et al, 2020). Furthermore, the work of Wanke and Santarcangelo (2021) reminds us that the vast majority of studies in this area to date have focused on Western tonal music (primarily pop music), whereas different approaches may be needed to understand the relationship between memory and other musical genres, such as contemporary art music.…”
Section: Discussionmentioning
confidence: 97%